2015
DOI: 10.1080/15384047.2015.1026483
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of nimotuzumab plus single agent chemotherapy as second- or third-line treatment or more in patients with recurrent, persistent or metastatic cervical cancer

Abstract: Nimotuzumab is a humanized IgG1 monoclonal antibody against the EGFR extracellular domain that has been evaluated in solid tumors as a single agent or in combination with chemotherapy and radiation. Cervical cancer patients who are refractory or progressive to first-line chemotherapy have a dismal prognosis, and no second-or thirdline chemotherapy is considered standard. This pilot trial aimed to evaluate the efficacy and safety of nimotuzumab in 17 patients with pre-treated advanced refractory or progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…A pilot study was conducted to evaluate efficacy and safety of nimotuzumab in combination with chemotherapy among Caucasian patients with advanced or progressive cervical cancer. 12 The results of this study showed that nimotuzumab is well tolerated and may have a role in the treatment of advanced cervical cancer. However, to date, there has been no study that evaluates the efficacy and safety of nimotuzumab in combination with chemoradiotherapy in Chinese patients with locally advanced cervical cancer.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…A pilot study was conducted to evaluate efficacy and safety of nimotuzumab in combination with chemotherapy among Caucasian patients with advanced or progressive cervical cancer. 12 The results of this study showed that nimotuzumab is well tolerated and may have a role in the treatment of advanced cervical cancer. However, to date, there has been no study that evaluates the efficacy and safety of nimotuzumab in combination with chemoradiotherapy in Chinese patients with locally advanced cervical cancer.…”
Section: Introductionmentioning
confidence: 70%
“…Overexpression of epidermal growth factor receptor (EGFR) in cervical cancer is well documented (overexpression ranges from 6% to 90%); this makes EGFR as a potential target in cervical cancer. 12 Nimotuzumab is a humanized IgG1 monoclonal antibody which blocks the activation of EGFR without intrinsic stimulating activity. Nimotuzumab displayed a longer plasma half-life with better safety profile when compared with other anti-EGFR antibodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This antibody has been extensively evaluated in patients with advanced cervical, head and neck, glioma, glioblastoma, lung, esophageal, pancreatic, and gastric cancers. [2][3][4][5][6][7] The main objectives of the studies performed to date have been to determine the toxicity, therapeutic effect, and biodistribution of the monoclonal antibody alone or as a delivery system for radioisotopes. Other studies have determined the in vivo specificity and the ratio of antibody uptake in tumor compared to normal tissues.…”
Section: Figurementioning
confidence: 99%
“…Nimotuzumab was well tolerated. There were no complete or partial responses observed; stable disease was found in 35% [34]. Study findings are limited as acceptability was addressed; however, study design excluded PFS and OS as endpoints.…”
Section: Expert Commentarymentioning
confidence: 99%